التسويق الزراعي الخارجي وأهميته في تنمية الصادرات الزراعية - عاشور، إيمان; بيشاري، كريم (جامعة محمد بوضياف المسيلة - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2018)
تتمتع الجزائر بمقومات زراعية هامة يمكن أن تجعل منها أكبر قوة اقتصادية زراعية عالمية، غير أن الصادرات الزراعية لا ترقى لهاته المقومات وتشكل المنتجات الغذائية الجزء الأكبر منها، كما أن مساهمة الصادرات الزراعية في إجمالي الصادرات ضعيفة جدا. لذا سعينا من خلال هذه الدراسة لإبراز أهمية ودور التسويق الزراعي الخارجي في ترقية هاته الصادرات، فالتطبيق الفعال للأنشطة التسويقية الزراعية الخارجية من بحوث ودراسات تسويقية بهدف جمع كل المعلومات والمعطيات المتعلقة بالأسواق الخارجية المستهدفة من عرض وطلب على المنتجات الزراعية والمواصفات والخصائص التي يجب أن تتصف بها من أجل تلبية حاجات ورغبات المستهلكين بالشكل المرغوب، إضافة إلى الترويج الدولي للتعريف بهاذه المنتجات وتمييزها عن منتجات المنافسين يمكن أنيساهم في تنمية الصادرات الزراعية.
Algeria has important agricultural resources that can make it the world's largest agricultural economic power. However, agricultural exports do not meet these resources and food products constitute the largest part of them. The share of agricultural exports in total exports is very weak. Therefore in this study, we sought to highlight the importance and role of external agricultural marketing in the promotion of agricultural exports. The effective application of the external agricultural marketing activities as marketing researches and studies in order to collect all the information and data related to the external markets targeted from the supply and demand of agricultural products and the specifications and characteristics that must be characterized by in order to meet the needs and desires of consumers as wanted, in addition to the international promotion to inform customers about these products and differentiate them from the products of competitors, which contributes to the development of agricultural exports.
Keywords: السياسة الزراعية -- الإرشاد الزراعي -- التسويق الزراعي الخارجي -- التنمية الزراعية -- الصادارات الزراعية -- الجزائر